Sociodemographic factors and perceived patient-provider communication associated with healthcare avoidance among women with psychological distress - Kobi V. Ajayi; Sonya Panjwani; Whitney Garney; Carly E. McCord (Elsevier, 2022)
Objective: To establish the extent to which psychological distress influences health avoidance behavior among women, controlling for patient provider communication and sociodemographic characteristics. Methods: Data from the 2019 Health Information National Trends Survey (HINTS 5, Cycle 3) was analyzed to obtain healthcare avoidance behavior among women aged 18 and older (n = 2788). Weighted descriptive, bivariate, and multivariable logistic regression models were conducted. Results: Approximately 649 women or 1 in 4 women (26.7% weighted prevalence; 95% Confidence Interval [CI] 0.23%-0.29%) avoided healthcare in the past 12 months. Non-Hispanic white (62.8%) and married (55.4%) women represented a higher proportion of the sample. Bivariate analysis revealed that the odds of reporting healthcare avoidance among women with mild, moderate, and severe psychological distress (Odds Ratio [OR]: 2.26, 95% CI: 1.45-3.53, p = 0.001; OR: 3.88, 95% CI: 2.29-6.56, p < 0.001; OR: 3.08, 95% CI: 1.81-5.23, p < 0.001) was significantly higher compared to those with none-minimal psychological distress. In the adjusted model, women with moderate and severe psychological distress (Adjusted OR [AOR]:3.15, 95% CI: 1.55-6.38, p = 0.002; AOR: 2.24, 95% CI: 1.10-4.92, p = 0.044) were more likely to report healthcare avoidance than those experiencing none-minimal psychological distress. Furthermore, increasing patient-provider communication score (AOR: 0.91, 95% CI: 0.87-0.96, p < 0.001) reduced the likelihood of healthcare avoidance. Among the sociodemographic variables assessed, being younger (18-49 years) and having less than a high school degree significantly increased the chances of avoiding healthcare. Conclusion: A high proportion of women with psychological distress avoid necessary healthcare. Patient-provider communication quality, increasing age, and being a high school student contribute to healthcare avoidance in women. Innovation: Strategies to improve health service utilization must address healthcare avoidance by developing effective health communication targeted at women with psychological distress.